Proceedings of OCEANS 2005 MTS/IEEE
DOI: 10.1109/oceans.2005.1640142
|View full text |Cite
|
Sign up to set email alerts
|

NOAA’S Ecosystem Approach to Management

Abstract: The National Oceanic and Atmospheric Administration's (NOAA) Ecosystem Approaches to Management (EAM) is a holistic, evolutionary management strategy designed to improve the productivity of coastal and marine ecosystems. NOAA has developed a vision for an ecosystem approach to management, and detailed its mission and outcomes for sustainable use of the nation's coastal and marine resources. This vision incorporates collaboration among NOAA, other federal, state, tribal, and local agencies, NGOs, academic and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Against the backdrop of pinniped interactions with listed fish and fishermen, NOAA has moved resource management to a broader strategy designed to improve the health and productivity of coastal and marine ecosystems. Known as "ecosystem-based management," NOAA has adopted this approach based on the fundamental understanding that an ecosystem is "a geographically specified system of organisms (including humans), their environment, and the processes that control their dynamics" (Burgess et al 2005). Because humans are also a player in NOAA's vision, it is important that the human dimension be factored into resource management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Against the backdrop of pinniped interactions with listed fish and fishermen, NOAA has moved resource management to a broader strategy designed to improve the health and productivity of coastal and marine ecosystems. Known as "ecosystem-based management," NOAA has adopted this approach based on the fundamental understanding that an ecosystem is "a geographically specified system of organisms (including humans), their environment, and the processes that control their dynamics" (Burgess et al 2005). Because humans are also a player in NOAA's vision, it is important that the human dimension be factored into resource management decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Managers in the Great Lakes basin were arguably at the forefront of EBM development (Slocombe ); EBM was later adopted by other management agencies in both countries (e.g., National Oceanic and Atmospheric Administration [USA], Fisheries and Oceans Canada; Burgess et al. ; O'Boyle and Jamieson ).…”
Section: Ecosystem‐based Management In the Great Lakes Basinmentioning
confidence: 99%
“…The adoption of this innovative socialecological perspective demonstrated that scientists, managers, and policymakers viewed the Great Lakes as an integrated system, which needed to be sustainably managed for ecological and human health. Managers in the Great Lakes basin were arguably at the forefront of EBM development (Slocombe 1998 ); EBM was later adopted by other management agencies in both countries (e.g., National Oceanic and Atmospheric Administration [USA], Fisheries and Oceans Canada; Burgess et al 2005 ;O ' Boyle and Jamieson 2006 ).…”
Section: Ecosystem-based Management In the Great Lakes Basinmentioning
confidence: 99%